Rhinovirus Suppresses TGF-β-GARP Presentation by Peripheral NK Cells - Krammer, Susanne; Yang, Zuqin; Mitländer, Hannah; Grund, Janina; Trump, Sonja; Mittler, Susanne; Zirlik, Sabine; Neurath-Finotto, Susetta (Cells, 2023)
Asthma is a chronic airway disease whose exacerbations are often triggered by rhinovirus infection. TGF-β1 induces rhinovirus replication in infected cells. Moreover, TGF-β1 is a pleiotropic mediator that is produced by many immune cells in the latent, inactive form bound to the latency-associated peptide (LAP) and to the transmembrane protein glycoprotein A repetitions predominant (GARP). In this study we wanted to investigate the effect of rhinovirus infection on the TGF-β secretion and the downstream signaling via TGF-βRI/RII in peripheral blood mononuclear cells from control and asthmatic patients after rhinovirus infection ex vivo. Here, we found a significant upregulation of TGF-βRII in untouched PBMCs of asthmatics as well as a suppression of TGF-β release in the rhinovirus-infected PBMC condition. Moreover, consistent with an effect of TGF-β on Tregs, PBMCs infected with RV induced Tregs, and TGF-βRII directly correlated with RV1b mRNA. Finally, we found via flow cytometry that NK cells expressed less GARP surface-bound TGF-β, while cytokine-producing NKbright cells were induced. In summary, we show that rhinovirus infection inhibits TGF-β release in PBMCs, which results in the activation of both Treg and NK cells.
CRIS-Team Scopus Importer:2023-01-20
Keywords: asthma; NK cells; rhinovirus; TGF-β; TGF-β RI; TGF-β RII